Fatty Acid Composition and Antibacterial Activity of Swietenia Macrophylla King Seed Oil - M. M., Yusoff; Muhammed, B. Suliman; Nour, A. H.; Azhari, H. Nour; Kuppusamy, Palaniselvam; A. R., Yuvaraj; Adam, Mazza S. (Academic Journals, 2013)
Pathogenic bacteria cause many acute and serious diseases, especially ‘multiple-drug-resistant’ strains have become such a problem due to overuse of antibiotics. Various medicinal plants are used to prevent or cure infectious diseases. The aims of this study were to determine the oil content, fatty acids compositions, and antibacterial activity ofSwietenia macrophylla king seed oil against four multiple-drug-resistant bacteria namely:Staphylococcus aurous, Staphylococcus typhimurium, Pseudomonas aeruginosa andEscherichia coli by disk diffusion method. The lipids were extracted by soxhlet using diethyl ether and n-hexane; and their Free Fatty Acids (FFA) were analyzed by GC-MS. The oil content was 39 to 42.7% and major fatty acid compositions were linoleic (37.50 to 39.21%), oleic (18.82 to 22.03%), stearic (16.75 to 17.65%), and palmitic (14.62 to 15.47%) for diethyl ether and n-hexane, respectively. The antibacterial activity among seed oil was extremely broad and inhibition zones ranged from 0 to 20 mm. These results showed the potential of S. macrophylla seed oil as antimicrobial agent for certain types of bacteria such as S. typhimurium. Moreover, the TLC analysis showed the presence of others constituents such as sterols and this may warrant further research.